Parasites of firebugs in Austria with focus on the "micro"-diversity of the cosmopolitan trypanosomatid Leptomonas pyrrhocoris - Kostygov, Alexei Yu; Chmelová, Ľubomíra; Reichl, Julia; Jászayová, Alexandra; Votýpka, Jan; Fuehrer, Hans-Peter; Yurchenko, Vyacheslav (Parasitology research, 2023)
In this work, we investigated parasites of the firebug Pyrrhocoris apterus in Austria and demonstrated that in addition to the extensively studied Leptomonas pyrrhocoris, it can also be infected by Blastocrithidia sp. and by a mermithid, which for the first time has been characterized using molecular methods. This diversity can be explained by the gregarious lifestyle, as well as the coprophagous and cannibalistic behavior of the insect hosts that makes them susceptible to various parasites. In addition, we showed no tight association of the L. pyrrhocoris haplotypes and geographical locations (at least, considering the relatively small scale of locations in Austria) implying that the natural populations of L. pyrrhocoris are mixed due to the mobility of their firebug hosts.
Keywords: Mermithidae; Austria; Pyrrhocoris apterus; Firebugs; Heteroptera; Blastocrithidia; Trypanosomatina; paraziti; Animals; Parasites; Rakousko; zvířata